2005
DOI: 10.1097/01.tp.0000163506.40189.65
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Increases Functional β-Cell Mass by Improvement of Angiogenesis of Isolated Human and Murine Pancreatic Islets

Abstract: Optimized angiogenesis of islet transplants resulted in greater availability of insulin caused by beta-cell proliferation and a significantly higher percentage (90% versus 20%) of mice cured from diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 20 publications
4
116
0
Order By: Relevance
“…We have shown that normal isolated human islets express the VEGF receptors VEGF-R1, -R2 and -R3, as well as the coreceptor neuropilin 1. We have reproduced the recently described data on VEGF production in isolated human islets [35], yet our data suggest that VEGF is produced under standard culture conditions, in contrast to the hypoxic environment used in the study by Lai et al [35]. The expression of neuropilin 1 has previously been described in islet cells using immunohistochemistry of pancreas sections from chronic pancreatitis specimens [36].…”
Section: Discussionsupporting
confidence: 84%
“…We have shown that normal isolated human islets express the VEGF receptors VEGF-R1, -R2 and -R3, as well as the coreceptor neuropilin 1. We have reproduced the recently described data on VEGF production in isolated human islets [35], yet our data suggest that VEGF is produced under standard culture conditions, in contrast to the hypoxic environment used in the study by Lai et al [35]. The expression of neuropilin 1 has previously been described in islet cells using immunohistochemistry of pancreas sections from chronic pancreatitis specimens [36].…”
Section: Discussionsupporting
confidence: 84%
“…50 Several studies have previously demonstrated improved islet graft revascularization in response to the production of recombinant VEGF-A within the islets. 8,9 However, unlike other pretreatment procedures for introducing VEGF-A to the islets, such as gene therapy, 8,9,51 anchoring VEGF-A directly to immobilized heparin on the islet surface should not be associated with an increased risk of inducing adverse effects on islet function 52,53 or adaptive immune responses. Importantly, islet functionality was not affected by anchoring of VEGF-A in this study because the growth factor in combination with immobilized heparin did not affect insulin release in response to a glucose challenge.…”
Section: Figmentioning
confidence: 99%
“…[4][5][6] Growth factors, particularly vascular endothelial growth factor (VEGF), are known to contribute significantly to the vascularization of transplanted islets. [7][8][9][10][11] The VEGF family of homodimeric glycoproteins in humans consists of VEGF-A, -B, -C, -D and placental growth factor. VEGF-A is critical during development as shown by lethality of transgenic mice lacking one allele.…”
Section: Introductionmentioning
confidence: 99%
“…Several biological factors such as glucagon-like peptide-1, 53 VEGF, 27,[103][104][105][106] and hepatocyte growth factor/scatter 107,108 can be used to stimulate islet function. Other factors can also be used to create a more-conducive environment for transplantation.…”
Section: Additional Strategies To Increase Islet Cell Survival and Fumentioning
confidence: 99%